BUERGER ALLEN EXERCISE ON THE RISK OF INJURY IN THE FEET OF DIABETES MELLITUS TYPE 2 - Hapipah; Heriawan; Istianah; Dewi Nur Sukma Purqoti; Zaenal Arifin (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
Diabetes Mellitus is a chronic metabolic disease that requires medical care and self-management to prevent complications of diabetic ulcers. The Buerger Allen Exercise is a specific exercise that aims to increase circulation to the legs by using changes in gravity and using muscle contraction through active movements of the legs to increase circulation of peripheral blood vessels. The Inlow's 60-second Diabetic Foot Screen Tool is an indicator for assessing the risk of foot injuries. This study aims to determine the effect of Buerger Allen Exercise on the risk of foot injuries in patients with diabetes mellitus type 2 at Masbagik Health Center. The research design used a pre-experimental design with a one group pretest-posttest design. The sampling technique was purposive sampling with a sample of 18 respondents who met the inclusion criteria. Data analysis used univariate and bivariate analysis. The mean value of the risk of foot ulcers in diabetes mellitus respondents before the intervention was 9.00 with a standard deviation of 1.328 and after the intervention the mean value was 8.54 with a standard deviation of 1.286. The results of the Wilcoxon test show a p value: 0.000 which means that there is an effect of Buerger Allen Exercise on the risk of foot injuries in patients with diabetes mellitus type 2 and is hoped that the Buerger Allen Exercise intervention can be applied as an effort to prevent complications of diabetic foot ulcers in patients with DM type 2. Keywords: Diabetes Mellitus; Buerger Allen Exercise; Foot Wound Risk